The advent of the algorithm : the idea that rules the world - Berlinski, David, 1942- (New York : Harcourt, 2000)
"Here is the story of the search for and eventual discovery of the algorithm, the set of instructions that drives computers. An idea as simple as the first recipe and as elusive as the quark or the gluon, the algorithm was discovered by a succession of logicians and mathematicians working alone and in obscurity during the first half of the twentieth century."--BOOK JACKET.
ch. 1. The marketplace of schemes -- ch. 2. Under the eye of doubt -- ch. 3. Bruno the fastidious -- ch. 4. Cargoload and crack-up -- ch. 5. Hilbert takes command -- ch. 6. g ime against time --g rtifact of mind --g
Includes index.
Keywords: Algorithms